EVALUATION BY COMPETENCES AND THE ACHIEVEMENT OF LEARNING IN THE AREA OF COMMUNICATION IN STUDENTS OF COMPUTING AND INFORMATICS, AT THE PISCO INSTITUTE - Fajardo Cárdenas, Libia Maribel (2020)
The research set out to determine the influenceof the evaluation by competencies in the learning ofthe communication area in the students of computingand informatics of the Higher Pedagogical InstituteCarlos Medrano Vásquez” district San Clemente,Pisco Ica Region. We worked with a sample of 32students in a school context, with the scientific,statistical, inductive and deductive method. Dueto the depth of the study, it is descriptive andexplanatory of a non-experimental design. Datacollection was done using the evaluation technique,through the pedagogical test, where the reliabilityof the instrument was made using the Cronbach'salpha coefficient and the validity by expert judgment.The data were analyzed using the SPSS version24 program, hypothesis test with Student's t ofrepeated measurements. It was concluded that thecompetency assessment influences student learningby up to 80%, as it produces less stress and allowsself-reflection in the student due to the clarity of theresults of their performance.